Construction of a Potentiometric Glutamate Biosensor for Determination of Glutamate in Some Real Samples - Yilmaz, Demet; Karakus, Emine (INFORMA HEALTHCARE, 2011)
The potentiometric glutamate biosensor based on ammonium-selective poly(vinylchloride) (PVC) membrane electrode was constructed by chemically immobilizing glutamate oxidase. Ammonium ions produced after an enzymatic reaction were determined potentiometrically. We determined the optimum working conditions of the biosensor such as buffer concentration, buffer pH, lifetime, response time, linear working range, kinetic constants (K-m and V-max) of glutamate oxidase enzyme used for biosensor construction values, and other response characteristics. Additionally, glutamate assay in some real samples such as chicken bullion, healthy human serum, and commercial multipower amino acid mixture were also successfully carried out. The results showed good agreement with previously reported values.
Keywords: Glutamate oxidase; Glutamate biosensor; Enzyme electrode; Potentiometric; Glutamate determination; CAPILLARY-ELECTROPHORESIS; ELECTRODES; LACTATE; GLUCOSE; DOPAMINE; SYSTEM; BRAIN; ARRAY; Biotechnology & Applied Microbiology; Engineering; Materials Science